Effect of emotional intelligence on problematic mobile social media use: mediating role of peer relationships and experiential avoidance - Xin Chen; Sifan Peng; Hexu Guan; Huanran Sun; Hongxuan Wu; Xumei Yao; Zi Chen; Xi Yang (Frontiers in Psychology)
ObjectiveThe I-PACE model was employed as the theoretical framework to investigate the effect of emotional intelligence on problematic mobile social media use. Furthermore, this study explored whether peer relationships and experiential avoidance serve as mediating factors in this relationship.MethodsA total of 1,448 students from nine public universities across Chengdu, Beijing, Shanghai, and Kunming were recruited between May 1, 2021, and October 28, 2021, through convenience sampling. The survey instruments included the Emotional Intelligence Scale, the Peer Relationship Scale, the Acceptance and Action Questionnaire Second Edition, and the Problematic Mobile Social Media Use Assessment Questionnaire.Results(1) Emotional intelligence exhibited a negative correlation with both experiential avoidance and problematic mobile social media use, while it demonstrated a positive correlation with peer relationships; (2) Peer relationships were negatively correlated with both experiential avoidance and problematic mobile social media use, while experiential avoidance was positively correlated with problematic mobile social media use; (3) Peer relationships and experiential avoidance acted as mediators in this relationship, forming a sequential mediation chain and collectively influencing how emotional intelligence affects problematic mobile social media use.ConclusionThis study investigates the relationship between emotional intelligence and the severity of problematic mobile social media use among Asian participants. Peer relationships and experiential avoidance independently mediate and sequentially mediate the relationship between emotional intelligence and problematic mobile social media use. Emotional intelligence positively influences peer relationships, which subsequently negatively affects experiential avoidance, ultimately reducing problematic mobile social media use. Both peer relationships and experiential avoidance are shaped by emotional intelligence and further contribute to an individual’s problematic mobile social media use.